What are the Psychosocial Predictors of Not Drinking Alcohol in Iranian Adolescents? Applying the Theory of Planned Behavior - Narges Mobasheri; Leila Ghahremani; Abdolrahim Asadollahi; Mohammad Hossein Kaveh (Shiraz University of Medical Sciences, 2024)
Background: Alcohol consumption, as a high-risk behaviour of adolescents, is a problematic challenge in health system around the globe. Iran, as an Islamic country, has been faced with this issue despite strict religious norms and heavy laws and punishment, especially after the fundamental 1979 revolution. This study aimed to analyze and use theoretical model to identify the factors influencing the intention not to drink alcohol among adolescents in southern Iran.Methods: The cross-sectional study was conducted in mid- 2020 in southern Iran. The data were collected using available samples from among 763 tenth grade adolescents who visited health canters to receive health services upon entering school. Kolmogorov-Smirnov, Shapiro-Wilk test, independent sample t-test, and binary logistic regression (P<0.05) were the tests used in the study. The demographic and behavioral characteristics data were collected; also, alcohol consumption questionnaire based on TPB model was utilized.Results: The construct of theory of planned behavior could explain intention and alcohol consumption behaviour (P<0.001), and other predictors included high-risk behaviors in family (P<0.001), descriptive subjective norms (P<0.001), and the quality of the relationship with the family (P<0.001).Conclusion: Theory of planned behavior has a very good ability to predict the intention and behavior of drinking among adolescents, and that intention is the strongest predictor of behavior; father's behaviors in the family play a key role in adolescents drinking behavior. Therefore, it seems that improving the relationship between adolescents and parents should be on the agenda of policymakers.